The role of personal purpose and personal goals in symbiotic visions - Berg, Jodi L. (Frontiers in Psychology, 2015)
It is believed that symbiotic visions can drive employees and organizations toward a common objective based on the premise that people have a high level of self-motivation and engagement when they are working toward something very personal. The field of organizational development has been aspiring to help organizations and people align their visions for decades without much, if any, empirical support for the role of personal purpose and goals in the symbiotic relationship with a company vision. This qualitative study examines the role personal purpose and goals play in how high performing leaders align to their company’s vision. Whether and how senior managers articulate this alignment, and its correlation to their motivation and engagement, was examined. An observation was that most senior managers within organizations with a well-developed and widely known higher purpose vision are driven by something personal, identified as either personal goals or a personal purpose. One of the key findings is that personal purpose and goals, when aligned to a company vision, appear to impact motivation and engagement in different ways. When alignment is felt through the sense of the greater purpose, there is a deep, almost spiritual, commitment to making the world a better place and helping the organization contribute to that. This seems to motivate them to guide the organization towards its higher purpose vision. When alignment is felt through the organization’s alignment to one’s personal goals, there is a great sense of commitment to completing the steps or tasks necessary to move toward the vision, yet a clear delineation between work and life ambitions.